Therapeutic effect of Active Hexose-Correlated Compound (AHCC) combined with CpG-ODN (oligodeoxynucleotide) in B16 melanoma murine model. Issue 2 (December 2015) - Ignacio, Rosa Mistica; Kim, Cheol-Su; Kim, Young-Do; Lee, Hak-Min; Qi, Xu-Feng; Kim, Soo-Ki
Highlights Combined therapy of AHCC plus TLR9 agonist (CpG-ODN) is effective in melanoma. Combined AHCC and KSK-CpG ODN improves redox balance in murine melanoma. Combined AHCC and KSK-CpG ODN improves cytokine balance in murine melanoma.